If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -65 + -11x = -4x + 40 Reorder the terms: -65 + -11x = 40 + -4x Solving -65 + -11x = 40 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -65 + -11x + 4x = 40 + -4x + 4x Combine like terms: -11x + 4x = -7x -65 + -7x = 40 + -4x + 4x Combine like terms: -4x + 4x = 0 -65 + -7x = 40 + 0 -65 + -7x = 40 Add '65' to each side of the equation. -65 + 65 + -7x = 40 + 65 Combine like terms: -65 + 65 = 0 0 + -7x = 40 + 65 -7x = 40 + 65 Combine like terms: 40 + 65 = 105 -7x = 105 Divide each side by '-7'. x = -15 Simplifying x = -15
| Ln(4x-1)=6 | | 0.75m-5-0.50m=1 | | 15x-25(5)=-115 | | -21+5x=51+9x | | 3.5x=2800 | | 10x-15y=53 | | 4x-12=46 | | 6=20-2 | | 67=5q+7 | | -8-9x=16-10x | | 10v+4=44 | | 63=3(1-2y) | | -2x-9=6x-15 | | (x+5)(2x-1)(3x+4)=0 | | 54=(2w^2)(-3w) | | 7n^2+12n+5=0 | | 8v-9v=-22 | | 4x+3.5=7x+2.6 | | y=10.50x+150 | | 11c+10=6c | | -9(1.1x+2.2)+5(-3.3+4.4x)= | | 78.4=8p | | 8y=5y+21 | | -6+-3x=9 | | -30=-7(6z-4) | | Tan(x-10)=1 | | 2x-20=2x+40 | | Y-4x=11 | | 48X^2-108X+54=0 | | 4x=3x+55 | | 3x-40=2x+50 | | x^4+10x+9=0 |